The Well-Being of Left-Behind Children in Rural Sichuan, China - Ling , Long; Ah , Siti Hajar Abu Bakar; Omar , Noralina (Journal of Ecohumanism, 2024)
Chinese scholars focused on the status of children's subjective well-being. However, one significant gap is the need to measure comprehensive child well-being in China's backward economic rural areas. The study adopted a multidimensional child well-being approach and child-centred perspective to measure rural left-behind children's material, physical, educational, psychological, and social well-being and present the multidimensional well-being of left-behind children in rural China. The study adopted a quantitative approach, and the survey method was the preferred approach for this study. A multistage random sampling technique was used to choose the geographical location of the study, study area, and children as survey respondents. Four hundred eighty left-behind children aged 10 to 16 in Sichuan province, China, were selected for the study. The selected left-behind children experienced a high level of well-being domains, except for moderate educational well-being. However, pocket money, physical exercise, academic achievement, child welfare for education, social services, coping strategies, and activity engagement were the core targets to promote the left-behind children's well-being through improving social expenditure on children, empowering the child welfare system, and providing sufficient social services in school in China.